Influence of Microstructural Effect on Microvickers Hardness Properties of SiO2-Na2O-CaO (SNC) Waste Based Glass-ceramic - Nur Fadilah, Baharuddin Pallan; N F, Adnin; K A, Matori; Mansor, Hashim; F M, Idris; Idza Riati, Ibrahim; S N A, Rusly; M Z A, Khiri; Rodziah, Nazlan; N Hapishah, Abdullah; M S E, Shafie; R S, Aziz; et al. (IOP Publishing Ltd, 2018)
There are a lot of waste materials consist of silicate based such as coal combustion ash, slag from steel production, fly ash, mud, as well as glass cullet or mixtures to produce glass-ceramics. This research work using clam shell (CS) ash and soda-lime-silica (SLS) waste glass powder for fabricating novel SiO2-Na2O-CaO (SNC) glass-ceramic. The samples were composed of SLS (50%), Na2CO3 (30%), and CS (20%) in weight percentage via conventional melt-quenching technique and solid-state sintering technique. The samples were investigated via X-Ray Diffractometer (XRD), Field emission microscope (FESEM), and microvickers hardness tester. The samples were sintered at 550-950 °C to investigate the influence of microstructural effect on microvickers hardness properties at applied force 0.5 and 1.0 kgf. The optimal Vickers hardness properties at sintering temperature 850 °C due to high crystallization of SiO2 phase from the residual glass and CaO content enhanced the viscosity flow, high compactness of particles arrangement and densification of sample.